New dimensions in ecological economics integrated approaches to people and nature - Dovers, Stephen; Stern, David I., 1964-; Young, M. D. (Michael Denis), 1952-; Edward Elgar Publishing (Cheltenham ; Northhampton, Mass. : Edward Elgar Pub., 2003)
Drawing on the biophysical sciences, public policy, geography, economics, exploratory research and the behavioural sciences, this book offers reviews and prescriptions for the future of ecological economics, placing particular emphasis on complex sustainability problems.
pt. 1. First dimension : challenges and reviews -- pt. 2. Second dimension : reorientations and openings -- pt. 3. Third dimension : frameworks and applications.
Includes bibliographical references and index.
Keywords: Environmental economics; Electronic books